2019
DOI: 10.3390/foods8090406
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Oxidation Inhibition Capacity of 11 Plant Materials and Extracts Evaluated in Highly Oxidised Cooked Meatballs

Abstract: The underlying mechanism(s) behind the potential carcinogenicity of processed meat is a popular research subject of which the lipid oxidation is a common suspect. Different formulations and cooking parameters of a processed meat product were evaluated for their capacity to induce lipid oxidation. Meatballs made of beef or pork, containing different concentrations of fat (10 or 20 g 100 g−1), salt (2 or 4 g 100 g−1), subjected to differing cooking types (pan or deep frying), and storage times (1, 7, and 14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Jin et al (2014) reported that the addition of low percentages would not be effective to slow down lipid oxidation despite betalains content. Moreover, the synergic antioxidant effect of plant extract and vacuum packaging was confirmed by Corbo et al (2008). Martinez et al (2006) highlighted the connection between pigment oxidation and lipid oxidation: in fact, catalytic species involved in such process are generated through myoglobin oxidation.…”
Section: Articlementioning
confidence: 96%
“…Jin et al (2014) reported that the addition of low percentages would not be effective to slow down lipid oxidation despite betalains content. Moreover, the synergic antioxidant effect of plant extract and vacuum packaging was confirmed by Corbo et al (2008). Martinez et al (2006) highlighted the connection between pigment oxidation and lipid oxidation: in fact, catalytic species involved in such process are generated through myoglobin oxidation.…”
Section: Articlementioning
confidence: 96%
“…An additional method to estimate nutritional deterioration in shelf life studies is to analyse the characteristics of the lipid profile of the formulations, which would be correlated with the formation of hydroperoxides [ 18 ]. Both the analysis of fatty acid and cholesterol profile as well as the formation of hydroperoxides in prototypes with phenolic extracts are performed by comparing samples treated with antioxidants and samples without antioxidants (control).…”
Section: Effect Of Natural Leaf Extracts On the Quality Of Processed Meat Productsmentioning
confidence: 99%
“…In this regard, the extracts from the leaves of a wide variety of plants ( Azadirachta indica , Bidens pilosa , Camellia sinensis , Coriandrum sativum , Eugenia uniflora , Hippophae rhamnoides , Ilex paraguariensis , Juglans regia, Moringa oleifera , Olea europea , Origanum vulgare , Prunus cerasus , Ribes nigrum , Salvia leriifolia, Salvia Rosmarinus , Satureja hortensis , Urtica dioica , Vaccinium myrtillus , among others) have been studied for their in the elaboration of meat formulations, such as frankfurters, ground meat, hamburgers, meatballs, sausages, etc. [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This preliminary study provides an overview of the sensory acceptability of dry-cured belly by Slovenian consumers in relation to gender, as characterized by leanness and boar taint level. The latest study by Burri et al [17] tackles the subject of lipid oxidation known to affect the development and final qualities of meat and meat products [18]. Accordingly, the study by Burri et al [17] had two main objectives: (i) develop a relevant oxidized processed meatball model to study the effects of supplemented antioxidants, and (ii) investigate lipid oxidation in meatballs without and with a range of eleven plant materials and extracts at different concentrations.…”
mentioning
confidence: 99%
“…The latest study by Burri et al [17] tackles the subject of lipid oxidation known to affect the development and final qualities of meat and meat products [18]. Accordingly, the study by Burri et al [17] had two main objectives: (i) develop a relevant oxidized processed meatball model to study the effects of supplemented antioxidants, and (ii) investigate lipid oxidation in meatballs without and with a range of eleven plant materials and extracts at different concentrations. The authors conclude that antioxidant-rich plant materials and extracts can efficiently prevent lipid oxidation in processed-meat products, such as meatballs.…”
mentioning
confidence: 99%